Strategi Manajemen Humas Dalam Menciptakan School Branding Pada Sekolah Islam Terpadu - Sholihah, Tutut (J-MPI (Jurnal Manajemen Pendidikan Islam), 2018)
More and more quality schools have created intense competition in the management of educational institutions. To be able to compete, the school branding strategy is very important for schools primarily in private schools. SDIT Al-Furqan and SMPIT Al-Ghazalii Palangka Raya became the location of the study because it is one of the private schools that offers quality oriented to Islam, and has made rapid progress with various advantages, incised many achievements both in academic and non-academic terms, increasing number of participants each year. The problem raised in this study is how to plan public relations strategy, how to implement the public relations management strategy and how the results of implementing the public relations management strategy in creating School Branding in both schools. This study aims to describe and analyze the planning of public relations management strategies, implementation of the public relations management strategy and how the results of its implementation in creating School Branding at SDIT Al-Furqan and SMPIT Al-Gazali Palangka Raya, and to offer a concept of public relations management strategies in creating School Branding at Integrated Islamic schools. The study was conducted using a descriptive qualitative approach, data was collected through interviews, observation and documentation studies. The main subjects are principals, public relations, parents of students, heads of administration, teachers, and the community. The results of this study reveal that: 1) Public relations management strategy planning is designed and organized together with principals, divisions and public relations by considering all aspects until the school brand can reach the community, 2) Implementation of public relations management strategies carried out in accordance with the schedule organized by conducting promotions and publications in print media, electronic media, and social media, as well as communicating and socializing directly to the public, 3) The results of the public relations management strategy can be seen in the indicators of the success of schools becoming well-known in the community, creating a positive image for school, students increase every new school year, become a favorite and superior school.